El dialecto del color - Moscoso Guamán, Mario Gorki (Machala : Universidad Técnica de Machala, 2019)
The research work called "The Dialect of Color", has as its purpose to elaborate a strip that contains a chromatic alphabet, that allows to communicate through color the ideas, poems, historical and important facts of our environment. The urban regeneration of Machala, although it is true, has partly succeeded in modernizing the city urbanistically, it has not considered in its structure artistic works that identify the cultural ancestor of Machala and the province in general, so that they give it that stately appearance in the frame of their cultural values and perspectives to develop the arts and tourism.
El trabajo de investigación denominado “EL Dialecto del Color”, tiene como propósito elaborar una regleta que contenga un abecedario cromático, que permita comunicar a través del color las ideas, poemas, hechos históricos e importantes de nuestro medio. La regeneración urbana de Machala si bien es cierto ha logrado en parte modernizar urbanísticamente a la ciudad, no ha considerado en su estructura obras artísticas que identifiquen el ancestro cultural de Machala y la provincia en general, para que le den ese porte señorial en el marco de sus valores culturales y en perspectivas de desarrollar las artes y el turismo
Keywords: COLOR